1998
DOI: 10.1097/00007632-199805010-00021
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Considerations of Pedicle Screw Placement in the Thoracic Spine

Abstract: The Roy-Camille technique was associated with a high incidence of pedicle violation, whereas screw placement with a partial laminectomy significantly reduced the incidence of pedicle violation. Pedicle screw fixation in the thoracic spine remains a technical challenge and should not be used routinely. Screw placement with the open-lamina technique is recommended if pedicle screw fixation is strongly indicated in the thoracic spine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
115
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(120 citation statements)
references
References 16 publications
1
115
0
4
Order By: Relevance
“…These include the ''anatomical'' techniques such as the free hand method [24] and the openlamina technique [59]. The latter provides direct visualization of the medial wall of the pedicle.…”
Section: Discussionmentioning
confidence: 99%
“…These include the ''anatomical'' techniques such as the free hand method [24] and the openlamina technique [59]. The latter provides direct visualization of the medial wall of the pedicle.…”
Section: Discussionmentioning
confidence: 99%
“…The open-lamina technique described by Xu et al [25] allows direct visualization and palpation of the medial and superior pedicle walls. Although this technique gives additional anatomical information to the surgeon, it does not provide the anatomical alignment featured by the TDG.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccaro et al [22] found that the failure rate was highly variable between surgeons and that most of their own 41.1% misplaced screws violated the medial wall, some by as much as 8.5 mm. Xu et al [25] showed a decreased incidence of pedicle perforation with the open lamina technique (16.0%), as compared to the Roy-Camille technique (54.7%). Cinotti et al…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies evaluating thoracic placement have focused mostly in the lower thoracic region [1,4,12,16,17,19,26,29]. Furthermore, accuracy of thoracic pedicle screw instrumentation has been reported in several cadaveric populations [5,7,21,22,25,28,29,31,32], and with the use of assisted-navigation techniques [2,5,6,8,25]. While there is data on thoracic screw placement accuracy in the literature, we found little information specifically reporting on upper thoracic screws inserted in vivo on nondeformed spines.…”
Section: Discussionmentioning
confidence: 87%